Tinjauan Kelayakan Finansial Pada Hotel Berjenis Kondotel Studi Kasus : Proyek Pembangunan Kondotel Pekanbaru Park - Sulton, Eko syalahuddin; Taufik, Hendra; Sebayang, Mardani (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Pekanbaru economic growth is relatively advanced to make this city a place to invest in the calculated by the investors one of them is investment in the field of hospitality. Investment inthe hospitality sector has a big risk if not prepared thoroughly, this is because in its construction requires a very large capital, therefore it is very important to review and analyzethe financial feasibility. In this research, it is reviewed about the financial feasibility of Condotel type hotel, which is in Kondotel Pekanbaru Park which is a hotel owned jointly by several owner and managed by hotel manager and its profit and profit will be shared between fellow hotel owners and managers. Financial analysis is done by analyzing the calculation of Net present value, benefit cost ratio, internal rate of return, payback period and also sensitivity analysis. The results obtained are total investment kondotel Rp. 192.670.744.974,35 with NPV of Rp. 67.877.696.368,23, BCR of 1.2, IRR of 24,97% greaterthan the return current of 13.5% and PBP for 9 years 7 month 17 days (project plan life for 50 years). Overall the investment project for the development of Kondotel Pekanbaru Park is feasible to build with the hotel occupancy rate of 66%. Investor standard room or SMI get profit of Rp 33.102.537,58 / year and free stay for 21 point / year. While the investor room suite or SMI corner get a profit of Rp 40.138.145,99 / year and free stay for 21 point / year with discount payback period in year 14.Keywords: Financial Analysis, Condotel Pekanbaru Park, Occupancy Hotel, Sensitivity Analysis, Investor.